Enzyme activity profiling for physiological phenotyping within functional phenomics: plant growth and stress responses. (8th June 2022) - Jammer, Alexandra; Akhtar, Saqib Saleem; Amby, Daniel Buchvaldt; Pandey, Chandana; Mekureyaw, Mengistu F; Bak, Frederik; Roth, Peter M; Roitsch, Thomas
Abstract : Enzyme activity profiling datasets, when analysed and visualized to exploit their full potential, provide functional information on the regulation of plant development, abiotic stress response, and pathogen defence. Abstract: High-throughput profiling of key enzyme activities of carbon, nitrogen, and antioxidant metabolism is emerging as a valuable approach to integrate cell physiological phenotyping into a holistic functional phenomics approach. However, the analyses of the large datasets generated by this method represent a bottleneck, often keeping researchers from exploiting the full potential of their studies. We address these limitations through the exemplary application of a set of data evaluation and visualization tools within a case study. This includes the introduction of multivariate statistical analyses that can easily be implemented in similar studies, allowing researchers to extract more valuable information to identify enzymatic biosignatures. Through a literature meta-analysis, we demonstrate how enzyme activity profiling has already provided functional information on the mechanisms regulating plant development and response mechanisms to abiotic stress and pathogen attack. The high robustness of the distinct enzymatic biosignatures observed during developmental processes and under stress conditions underpins the enormous potential of enzyme activity profiling for future applications in both basic and applied research. Enzyme activity profiling will complement molecular -omics approaches to contribute to the mechanistic understanding required to narrow the genotype-to-phenotype knowledge gap and to identify predictive biomarkers for plant breeding to develop climate-resilient crops.